Anmeldelser - Hauge, Peter (Danish Yearbook of Musicology, 1998)
Review of: Jack Lawson: Carl Nielsen (20th-Century Composers, ed. Norman Lebrecht). Phaidon Press, London 1997. David Fanning: Nielsen: Symphony no. 5 (Cambridge Music Handbooks, ed. Julian Rushton). Cambridge University Press, Cambridge 1997.